Executive Summary: Utilizing Motivational Interviewing to Increase Pediatric Influenza Vaccine Uptake - Nolan, Alyssa Jane (My University, 2025)
DNP Executive Summary: Use for the paper required to fulfill the Doctor of Nursing Practice program.